2022
DOI: 10.5114/biolsport.2022.107479
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine supplementation improves physical performance without affecting fatigue level: a double-blind crossover study

Abstract: This study examined the effect of caffeine supplementation (CAFF) in a Wingate test (WT), and the behaviour of blood lactate concentrations (BLa) and neuromuscular fatigue (NMF), measured as reduced countermovement jump (CMJ) performance, in response to the WT. In a double-blind crossover study, 16 participants attended the laboratory twice, separated by a 72-hour window. In the sessions, participants first ingested 6 mg·kg -1 of either CAFF or placebo (PLAC), and then performed a WT. BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…The current study ascertained that 6 mg/kg of caffeine increased vertical jump and change of direction performance, which is parallel to previous studies ( 9 , 34 , 35 ) and is in contrast to the other in which the participants were recreationally active young males who were not habituated to caffeine ( 36 ). This lack of significant difference in the abovementioned study may have resulted from the participants’ status as non-responders to caffeine.…”
Section: Discussionsupporting
confidence: 82%
“…The current study ascertained that 6 mg/kg of caffeine increased vertical jump and change of direction performance, which is parallel to previous studies ( 9 , 34 , 35 ) and is in contrast to the other in which the participants were recreationally active young males who were not habituated to caffeine ( 36 ). This lack of significant difference in the abovementioned study may have resulted from the participants’ status as non-responders to caffeine.…”
Section: Discussionsupporting
confidence: 82%
“…However, some evidence from several studies is not congruent with the results of the present study. It has recently been reported that acute CAF intake increased jump performance and anaerobic effort [52]. Also, De Salles Painelli et al [53] reported improved CM performance and total repetitions.…”
Section: Discussionmentioning
confidence: 94%
“…Collectively, the lack of ergogenic effect of CAF in jump performance may be attributed to the low specificity of the dryland modalities, which may not have been transferred to the jump performance, although it seems to provide improvement in swimming performance. In fact, previous studies indicated an improvement in jump performance, and such studies enrolled several experimental groups including trained volleyball players [55,56,59], active males with resistance training [48,52], well-trained high jumpers [54], soccer players [57], collegiate athletes [58], and elite Brazilian Jiu-Jitsu athletes [20]. Given the fact that the dryland nature of both team and individual sports comprises speed, repeated sprint ability, agility, balance, muscular strength, acceleration, jumping, and explosive power, the ergogenic effect of the CAF in these studies may have resulted from participants' responsiveness to the tests identical to the movement patterns and biomechanical demands in their sports.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Collomp et al 19 showed that trained swimmers were able to improve swimming sprint velocity with CAF ingestion while untrained counterparts did not experience ergogenic effects. Although unknown at this time, this may in part be explained by differences in muscle-buffering capacity since trained individuals may be able to buffer excess hydrogen ions formed from CAF-induced increases in lactate production and catecholamine release, in concert with increased Ca2 + bioavailability 20 , 21 . Still, others have suggested little to no differences in exercise responses with CAF leaving conclusions from this area convoluted and ambiguous 22 .…”
Section: Introductionmentioning
confidence: 99%